Large Scale Measurement of the Total Antioxidant Capacity of Different hungaricum Fruit and Vegetable Samples with Photochem Chemiluminometric Device - Veres, Zsuzsanna; Domokos-Szabolcsy, Éva; Fári, Gábor Miklós (Acta Agraria Debreceniensis, 2005)
In our present study, we performed a quick test of the antioxidant capacity of domestic fruit and vegetable cultivars with a PHOTOCHEM® instrument (Analytik Jena AG, Germany). The instrument is special because it can measure both the total lipid-soluble antioxidant capacity (ACL method) and the total water-soluble antioxidant capacity. Another advantage of the system is its quick measurement. With similar instruments, such measurement can take several hours, while PHOTOCHEM® can perform it within a few minutes.In our model studies, we examined the changes in the antioxidant capacity of sour cherry, green pepper, carrot, pumpkin, red beet and Brassica sp. cultivars. We aimed to determine how suitable the instrument is for quick, routine measurements in the case of the different horticultural products and which species have high antioxidant capacity values.On the basis of our examinations, we can state that the PHOTOCHEM® system is suitable for routine, semi-automated measurements of the total antioxidant capacity at several vegetables and fruits. Besides this, the system can be used for testing the quality of food products, for monitoring storability in post-harvest technologies, and for special breeding programmes and for physiological and biotechnological studies.